2017
DOI: 10.1186/s13018-017-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

Anteromedial versus transtibial technique in single-bundle autologous hamstring ACL reconstruction: a meta-analysis of prospective randomized controlled trials

Abstract: BackgroundThe aim of this study was to compare the clinical outcome and postoperative complication between single-bundle anterior cruciate ligament (ACL) reconstruction with an anteromedial (AM) technique and a transtibial (TT) technique.MethodsThe study includes clinical randomized controlled trials comparing the clinical outcomes of ACL reconstruction using the autologous hamstring tendon with an AM method and a TT method published up to September 2017 were retrieved from PubMed, Cochrane Library, and Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 41 publications
3
41
0
1
Order By: Relevance
“…Medial resection + lateral repair 1 3Medial repair + untreated medial tear 4 (11) Lateral repair + untreated lateral tear 3 (8) Total (n) 38…”
Section: Meniscal Injury Typementioning
confidence: 99%
“…Medial resection + lateral repair 1 3Medial repair + untreated medial tear 4 (11) Lateral repair + untreated lateral tear 3 (8) Total (n) 38…”
Section: Meniscal Injury Typementioning
confidence: 99%
“…Alerton et al reported better short term results with Trans-portal technique but no difference at mid and long term follow-up [20] . A metaanalysis of 5 RCTs by Chen et al concluded that in terms of postoperative stability and functional recovery of the knee the outcome of single-bundle ACL reconstruction with the AM technique is better than that with the TT technique [21] However at present there isn't enough clinical evidence to support one technique over the other. Trans-tibial technique is an easily reproducible, safe and technically less demanding and time tested.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010 there are many research [9] have reported the comparison between anteromedial and the transtibial and some of them show that the AM technique may have a superior outcome, last year two meta-analysis [10,11](up to 2015) get agreement on the results that based on the physical examination and scoring system results the AM technique is superior to the TT technique. But the RCT and the retrospective results in recent year also lead a idea that the two technique have no clinical differences.…”
Section: Introductionmentioning
confidence: 94%